Book review “R. Bessant, J. Tidd, Entrepreneurship, Il Mulino, 2020. Authorised translation from the english language edition published by John Wiley & Sons Limited” - Vannoni, Valeria (Piccola Impresa / Small Business, 2023)
The book faces the topic of entrepreneurship, with a focus on creating new successful businesses. After a theoretical framework of the topic, it provides practical indications about the tools to be used and the issues to be considered to develop an entrepreneurial project and bring it to success. The book is full of references to business cases that make it even more interesting to read.